Understanding geologic carbon sequestration and gas hydrate from molecular simulation / by Yongchen Song, Cong Chen and Wenfeng Hu - Song, Yongchen; Chen, Cong; Hu, Wenfeng
Understanding Geologic Carbon Sequestration and Gas Hydrate from Molecular Simulation systematically introduces CO2 geological sequestration and gas hydrate at the molecular-scale, with research including interfacial properties of multiphase, multicomponent systems, hydrogen bonding properties, adsorption characteristics of CO2CH4 in the pore, kinetic properties of decomposition/nucleation/growth of gas hydrate, the influence of additives on gas hydrate growth dynamics, and hydrate prevention and control technology. This book focuses on research-based achievements and provides a comprehensive look at global progress in the field.
Includes references and index
Keywords: Gas hydrates; Hydrogen bonding; Adsorption; Hydrogen bonding